Criterion for Controlling the Stress-Strain State of Composite Dielectric Materials Using the Effective Filtration Method; Key Engineering Materials; Vol. 781 : Radiation-Thermal Effects and Processes in Inorganic Materials - Surzhikov V. P. Vladimir Petrovich (2018, 2018)
Title screen